WAQF’S ROLE IN PROVIDING KEY URBAN FACILITIES - Zaman, Mahbuba (International Journal of Sukuk and Waqf Research, 2020)
At the beginning of the classical Ottoman era, the waqf institution had already reached its form, supported by a legal, administrative and operational structure, and the institution was already widespread in the Ottoman territories. Individually established autonomous waqf had already gained a primary role in the development of key urban facilities in Islamic cities. During the classical Ottoman era, while the state carried out essentially military constructions, including castles and fortifications, palaces for the royal family and public infrastructure such as roads and bridges; religious, educational, commercial, health and charity buildings for the public’s welfare were constructed via the waqf.